Advances in hormone replacement therapy: making the menopause manageable - Palacios Santiago (BMC, 2008)
Abstract The importance of the results of some large, randomized controlled trials (RCTs) on Hormone Replacement Therapy (HRT) has modified the risk/benefit perception of HRT. Recent literature review supports a different management. The differences in age at initiation and the duration of HRT are key points. HRT appears to decrease coronary disease in younger women, near menopause; yet, in older women, HRT increases risk of a coronary event. Although HRT is a recognized method in the prevention and treatment of osteoporosis, it is not licensed for the prevention of osteoporosis as a first-line treatment. The effectiveness of low and ultra-low estrogen doses has been demonstrated for the treatment of vasomotor symptoms, genital atrophy and the prevention of bone loss, with fewer side-effects than the standard dose therapy. Further research, however, is needed to determine the effect both on fractures, as well as on cardiovascular and breast diseases. Newer progestins show effects that are remarkably different from those of other assays. The effectiveness of testosterone at improving both sexual desire and response in surgically and naturally postmenopausal women is shown by the testosterone patch. The intention, dose and regimen of HRT need to be individualized, based on the principle of choosing the lowest appropriate dose in relation to the severity of symptoms and the time and menopause age.